Procurement of camelid fiber in the hyperarid Atacama Desert coast: Insights from stable isotopes. (20th May 2020) - Gayo, Eugenia M.; Martens, Tracy; Stuart-Williams, Hillary; Fenner, Jack; Santoro, Calogero M.; Carter, Christopher; Cameron, Judith
Abstract: Pastoralism and camelid management are traditionally attributed to the sociopolitical, economic and cosmovision of Andean populations, rather than to lowland hunter gatherer societies, living on the Pacific coast where camelid hunting is considered a marginal activity, and husbandry is a difficult enterprise given the hyper-arid conditions of lowland terrestrial ecosystems. Contrary to this interpretative historical view, our stable isotope analyses applied to 48 camelid fiber samples, suggests this highly valued camelid byproduct was obtained from camelids sustained on lomas vegetation formations during the Archaic (ca. 6500-4000 cal yr BP), Formative (ca. 4000-1500 cal yr BP) and Late periods (ca. 660-480 cal yr BP). Highlights: Coastal fog/lowland resources supported pre-Hispanic populations of camelids. Camelid fiber is not a reliable proxy for exchange with highland groups in the Coastal Atacama's northern valleys. Northern Chile's coastal population was selective in adopting technologies and practices introduced in the Formative Period. Camelid fiber was more accessible to northern Chile's marine hunter gatherers than previously indicated. The geographic source of camelid fiber is consistent across the Archaic, Formative and Late Periods.